Credibility and Authenticity of Digitally Signed Videos in Traffic - Grgurević, Ivan; Stančić, Adam; Škorput, Pero (Promet - Traffic&Transportation)
The paper presents the possibilities of insuring the credibilityand authenticity of the surveillance camera video by digitalsigning, using the public key infrastructure as part of interoperabletraffic and information system in the future intelligenttransport systems. The surveillance camera video is a sequenceof individual frames and a unique digital print, i. e. hash valueis calculated for each of these. By encryption of the hash valuesof the frames using private encryption key of the surveillancecentre, digital signatures are created and they are stored in thedatabase. The surveillance centre can issue a copy of the videoto all the interested subjects for scientific and research workand investigation. Regardless of the scope, each subsequentmanipulation of the video copy contents will certainly changethe hash value of all the frames. The procedure of determiningthe authenticity and credibility of videos is reduced to the comparisonof the hash values of the frames stored in the databaseof the surveillance centre with the values obtained from the interestedsubjects such as the traffic experts and investigators,surveillance-security services etc.